Analysis of viability and safe use of regenerated water andbiosolids in agriculture and restoration of degraded soils inthe La Villa river basin of the Republic of Panama - Opolenko, Valentina; Jiménez, Antonia; Rodríguez, María José (Revista Geográfica de América Central., 2025)
The objective of the research carried out was to establish the technical and economic advantages of using post-treated water, from the Chitre Wastewater Treatment Plant (WWTP), in agricultural irrigation, in addition to sludge as organic fertilizer in cropsand the recovery of degraded soil. The experimental plots were installed, planted with corn and grass, which were fertilized with different doses of biosolids and with nutrient-rich water, post-treated in artificial wetlands. Among the most relevant findings, the in-creased productivity of maize crops fertilized with biosolids stands out, reaching yields comparable to those achieved through technified agriculture. Additionally, there was a significant improvement in the nutritional quality of the forage and in the fertility of degraded soils within the albina ecosystem, which supported the successful development of plant species adapted to these conditions. These achievements not only sustainably contribute to food security but also promote the transition toward a circular economy in the coastal area of the Los Santos district, in the context of climate change adaptation.